The Power of Self-Efficacy and Its Impact on Adolescent Hedonistic Lifestyle - Sari, Erlina; Syahputra, Yuda; Hamam, Hamam; Ahiruddin, Ahiruddin; Rahmat, Candra Prasiska (JITSS (Journal of Innovation and Trend in Social Sciences), 2025)
The increasing tendency of adolescents to adopt a hedonistic lifestyle, characterized by hedonistic behavior and the pursuit of pleasure, has become a concern in schools. One factor that can counteract this tendency is self-efficacy, or an individual's belief in their ability to regulate behavior and face challenges. This study aims to identify the self-efficacy profile of eleventh-grade students at SMAN 44 East Jakarta, describe their hedonistic lifestyle tendencies, and examine the influence of self-efficacy on this lifestyle. The population consisted of 120 students, with a sample of 80 selected using the Slovin formula and purposive sampling. The research instruments included the Self-Efficacy Scale (SES), based on Bandura's indicators (magnitude, generality, strength), and the Hedonistic Lifestyle Scale (HLS), based on Engel's indicators (consumption, pleasure seeking, peer conformity). Instrument validity was tested with Pearson correlation and reliability with Cronbach's Alpha, resulting in α = 0.87 for self-efficacy and α = 0.85 for hedonistic lifestyle. Data were analyzed using descriptive statistics (mean, percentage, and distribution by gender) and simple linear regression with SPSS. The results showed that self-efficacy had a significant and negative effect on hedonistic lifestyle (p = 0.01 < 0.05), with R² = 0.390. This indicates that self-efficacy explains 39% of the variance, while 61% is influenced by other factors. These findings highlight the importance of strengthening self-efficacy to reduce students' hedonistic tendencies, which provides practical implications for guidance and counseling interventions in schools.